PENGARUH PENEMPATAN KARYAWAN DAN PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BANK DANAMON CABANG LUBUKLINGGAU - Ronal Aprianto; Dika Ardani (Jurnal Media Ekonomi (JURMEK), 2017)
Employee Placement has not yet matched the level of education achieved by employees with the work provided by the company, and also still lack of experience in completing work. Furthermore, promotion of positions given less attention to the elements of education and work performance achieved by employees and employee work performance is still not optimal. This research was conducted to determine the Effect of Employee Placement and Job Promotion on Employee Performance at PT. Bank Danamon Lubuklinggau Branch. In this study, a three-item variable questionnaire method was used, namely Employee Placement (X1), Job Promotion (X2), and Employee Performance (Y) using the SPSS 17.0 Program. The data analysis technique used is the Analysis of Multiple Linear Regression, Determination Coefficient (R2), and F Test. From the results of Multiple Regression Analysis the equation Ŷ = 3.685 + 0.743X1 + 0.149 X2 is obtained.